P-182 Developing a sustainable model of care for patients with end-stage heart failure. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Sturt, Wendy; Horne, Gill; Sykes, Jo; Chester, Tim
Abstract : Aims and objectives: This 18-month project aimed to enhance the opportunities for patients with end-stage heart failure (HF) and families to benefit from hospice and supportive care services to help them plan and experience better end-of-life care. Method: The HF service, care of older people, primary care, hospital palliative care, patients and families and hospice representatives, worked alongside a project lead designing a model of care and pathway for people with end-stage HF. A new Supportive and Palliative Care in Heart Failure MDT was established, providing an interdisciplinary forum for identification of those at the end-of-life, and aiding referral to specialist palliative care services. A patient information leaflet was designed and printed. Education was also provided for the HF Team on palliative/end-of-life care and end-stage HF management for the specialist palliative care services. Outcomes/impact: There is now an established pathway for patients, improved understanding and communications between the HF and specialist palliative care teams. The MDT meeting is held twice monthly and specialist palliative care referrals have more than doubled during the project. Patients and their families have access to core information about hospice and other end-of-life care services in their locality. Documentation audits of advance care planning discussion demonstrate that 64% of patients reviewed at the MDT had discussions about their wishes. However, more work is required as less than half of the patients had entries on the Electronic Palliative Care Coordination System and only 6% had documented evidence of their wishes. Feedback - such as ' All care and treatment have been excellent .' (Patient) and ' Much better links between heart failure team and palliative care team with great benefits for patients ' (Staff) - indicates that this collaborative project has been a positive experience, enabling more patients and families to access hospice and other end-of-life care services in their locality.